Piloting an interprofessional chronic pain management program: Perspectives of health students and community clients. Issue 6 (2nd November 2021) - Bridgman, Heather; Todd, Anne; Maine, Greer; Hardcastle, Sibella; Bird, Marie-Louise; Radford, Jan; Marlow, Annette; Elmer, Shandell; Murray, Sandra; Norris, Kimberley; Dean, Tracey; Williams, Andrew
ABSTRACT: Interprofessional learning (IPL) is vital for developing work-ready graduates of tertiary health professions and enhancing outcomes of patients with chronic pain. Twenty-two students from six health professions participated in or co-facilitated components of a 6-week group chronic pain management program. Twelve community clients with chronic pain and one family member participated. The program was piloted through the University of Tasmania Exercise Physiology Clinic and consisted of an initial assessment, weekly 1-hour group education sessions, and a 1-hour individualized, supervised exercise session. The program was evaluated using a constructivist approach via an investigator developed survey. Seven students and nine clients responded. A conventional content analysis was undertaken. Three categories were identified from students: Importance of IPL, Understanding Chronic Pain, and Improvement Suggestions. Three categories were identified from clients including Beneficial Aspects, Positive Peer Support, and Positive Pain Outcomes. Results indicate the program was beneficial for student learning and improved pain outcomes for participants. The model demonstrates value to student IPL and the potential to flexibly offer a real-world learning experience across many health professions, whilst addressing some of the common challenges associated with implementing IPL within curricula. The outcomes offer ways to explore sustainable implementation of the program long term.